A SUCCESSFUL GROWTH OF THE E-LEARNING SYSTEM AT UNIVERSITY OF MORATUAWA - Sarveswaran, K.; Perera, G.I.U.S.; Fernando, M.S.D. (Department of Computer Science & Engineering, 2002)
A successful e-Learning system primarily consists of a Learning Management system and a Content Management system. A Learning Management System addresses the user administration and related managerial requirements. This may include student registration and management, student enrollment, subject management and offering management. Content Management systems mostly cover the learning content managements. When we consider the e-Learning concept, all the content provided for learning should be in the soft form namely; soft versions of a document, e-book, audio or video file etc. This could be an easy solution to the perceived lack of updating of content. Despite that the content of some subject areas do not change regularly, many modern subject contents required to be updated frequently. In recent years, especially since 2002, many educational institutions focusing on a new educational phenomenon called blended learning. In traditional educational system, knowledge sharing was done in an instructor-led manner. The blended learning, which advanced the virtual class room learning trend, shared the knowledge through confronting each other, virtual class rooms and through various social activities like Wiki, Forum, Chat, etc. Many studies have been proven that the blended learning is more effective than tutor-led and virtual class room knowledge sharing methodologies [1]. The blended learning approach also acquires the social constructivist learning phenomenon. According to that phenomenon, learners are considered to be active participants seeking meaning and instructors tailor their teaching strategies to student responses and encourage students to analyze, interpret, and predict information. Also teachers rely heavily on open-ended questions and promote extensive dialogue among students [2].